Upaya Pemerintah Daerah untuk Meningkatkan Cakupan Desa ODF (Open Deﬁ cation Free) di Kabupaten Muaro Jambi, Sumedang dan Lombok Barat - Mugeni sugiharto; Nurhayati Nurhayati (Buletin Penelitian Sistem Kesehatan, 2019)
Introduction: The ODF (open defecation free) village to realize a healthy environment in preventing diarrheal diseases.This study aims to. Local government support is very important to accelerate the increase in the number of ODF village coverage. The purpose of this study is to find out the efforts of the regional government to realize the ODF village. This type of research is descriptive, using secondary data obtained and interviews. Research sites in Muaro Jambi, Sumedang and West Lombok Regencies, 2016. ODF villages have progressed along with increasing government support and community participation in encouraging stop open defecation free (SODF). The coverage of SODF people in 2016 in Muaro Jambi Regency was 78.07%, in Sumedang Regency 79.53%, and in West Lombok Regency 85.16%. Innovations to accelerate the realization of ODF villages include regulations, giving prizes, cooperating with NGOs and local entrepreneurs to make sanitation shops and sanitation savings and credit cooperatives, and providing punishment for people who break the agreement to stop defecating. The support of the local government by making innovative activities has accelerated the increase in the coverage of ODF villages in each district. Local government support and community participation are very important to realize the ODF village. ABSTRAK Program desa ODF (open defication free) untuk mewujudkan lingkungan sehat dalam mencegah penyakit diare. Dukungan pemerintah daerah sangat penting untuk percepatan peningkatan jumlah cakupan desa ODF. Tujuan penelitian ini adalah mengetahui upaya pemerintah daerah untuk menwujudkan desa ODF. Jenis penelitian diskriptif, menggunakan data sekunder diperoleh dan wawancara. Lokasi penelitian di Kabupaten Muaro Jambi, Sumedang dan Lombok Barat, tahun 2016. Terdapat kemajuan desa ODF seiring dengan meningkatnya dukungan pemerintah dan peran serta masyarakat menggalakkan stop buang air besar sembarangan (SBS). Cakupan masyarakat SBS tahun 2016 di Kabupaten Muaro Jambi 78,07%, di Kabupaten Sumedang 79,53%, dan di Kabupaten Lombok Barat 85,16%. Inovasi untuk percepatan mewujudkan desa ODF diantaranya menerbitkan regulasi, pemberian hadiah, kerja sama dengan LSM dan pengusaha lokal membuat toko sanitasi dan koperasi simpan pinjam sanitasi, dan memberikan sangsi bagi masyarakat yang melanggar kesepakatan stop buang air besar. Adanya dukungan pemerintah daerah dengan membuat kegiatan inovatif , telah mempercepat peningkatan cakupan desa ODF disetiap kabupaten. Dukungan pemerintah daerah dan peran serta masyarakat sangat penting untuk mewujudkan desa ODF.